Observance of enhanced specific capacity in quenched Cr doped CuFeO2. (1st March 2022) - Ramesh, Manickam; Kesavan, Thangaian; Biswas, Krishnendu
Abstract: The delafossite compound CuFeO2 (Cu 1+ ) is usually synthesized using controlled atmospheric conditions to avoid the more thermodynamically stable oxide CuFe2 O4 (Cu 2+ ). Herein we report the synthesis of CuFeO2 by a high-temperature solid state reaction method followed by rapid quenching to room temperature. The obtained powders are analyzed by XRD, SEM and XPS to ascertain phase formation, surface morphology and oxidation states of the elements respectively. The electrochemical performance of CuFe1-x Crx O2 (0 ≤ x ≤ 0.15) compounds are investigated for application in Li ion batteries as an anode material. A maximum initial specific capacity of 760 mA h.g −1 with a stability beyond 60 cycles is obtained for the x = 0.15 composition. It is believed that Cr doping increases the cyclic stability and specific capacity of CuFeO2 by creating more reaction sites owing to its de-sintering nature.